Political consciousness is the perception of political stability (The Peerian Journal, 2022)
This article describes the formation of political consciousness, its characteristics and its reaction to the political events taking place in society. Also, the connection of political consciousness with social practice and the relationship to social and political processes in society are summarized on a scientific and creative basis.